EFFECT OF 1,5-BIS(3,5-DIMETHYLPYRAZOL-1-YL)-3-OXAPENTANE DIACETATOCOPPER ON THE STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF THE LIVER AND PANCREAS IN RATS UNDER EXPERIMENTAL CONDITIONS - A. E. Nofal; N. D. Ovcharenko (Acta Biologica Sibirica, 2016)
Various factors including chemical substances affecting on the human and animal organisms, causing a series of changes in the structural and metabolic processes. Chemical compounds cause a violation in the homeostatic regulatory systems, liver function and also influences the metabolism of hormones produced by the gonads in experimental animals. These studies suggest that, the intraperitoneal administration rats by 1,5-Bis(3,5-dimethylpyrazol-1-yl)-3-oxapentane diacetatocopper (dose 12 mg per kg of body weight for 6 weeks) led to disturbance of the normal structure of the liver and pancreas. This drug caused intensively neutrophilic infiltration around venous vessels with bleeding, endoplasmic vacuolation of most cells, karyopyknosis, karyorrhexis, and karyolysis, as well as, increasing the amount of binucleated cells. This treatment led to a reduction in the total protein content in the tissue of liver and pancreas, as well as activation of the apoptotic process in liver cells.